2021
DOI: 10.3390/ijms22063154
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Plant Growth-Promoting Rhizobacteria (PGPR) in Stimulating Salinity Stress Defense in Plants: A Review

Abstract: To date, soil salinity becomes a huge obstacle for food production worldwide since salt stress is one of the major factors limiting agricultural productivity. It is estimated that a significant loss of crops (20–50%) would be due to drought and salinity. To embark upon this harsh situation, numerous strategies such as plant breeding, plant genetic engineering, and a large variety of agricultural practices including the applications of plant growth-promoting rhizobacteria (PGPR) and seed biopriming technique ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
74
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(78 citation statements)
references
References 174 publications
(228 reference statements)
3
74
0
1
Order By: Relevance
“…High α-tocopherol content in microbial inoculated plants lowers lipid peroxidation [ 26 ] as the α-tocopherol involves in scavenging lipid peroxyl radicals. PGPB enhanced salinity tolerance in plants by increasing the production of non- enzymatic antioxidants such as α-tocopherol, ascorbate, carotenoids and polyphenols [ 35 ]. P. indica colonization in maize plant decreased the level of MDA production by stimulating antioxidant enzymes [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…High α-tocopherol content in microbial inoculated plants lowers lipid peroxidation [ 26 ] as the α-tocopherol involves in scavenging lipid peroxyl radicals. PGPB enhanced salinity tolerance in plants by increasing the production of non- enzymatic antioxidants such as α-tocopherol, ascorbate, carotenoids and polyphenols [ 35 ]. P. indica colonization in maize plant decreased the level of MDA production by stimulating antioxidant enzymes [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Superoxidase dismutase (SOD, EC 1.15.1.1) is mainly involved as O 2 •− scavenger, which generates H 2 O 2 and O 2 . Therefore, H 2 O 2 can be scavenged by catalase (CAT EC 1.11.1.6), ascorbate peroxidase (APX, EC 1.11.1.11) and guaiacol peroxidase (GPX, EC 1.11.1.7) [ 65 , 87 ]. It has been reported that the increase in ABA production in plants under salinity stress induces antioxidant defense genes such as APX, SOD or CAT to remove ROS molecules [ 85 ].…”
Section: Climate Change and Its Impact On Agriculturementioning
confidence: 99%
“…PGPR promote plant growth by associative nitrogen fixation, phosphate solubilization, phytohormone production, and volatile organic compounds [29][30][31][32]. PGPR also neutralize stress in plants created by biotic and abiotic factors by boosting nutrient uptake, osmolyte accumulation, enhanced production of antioxidant enzymes, and metabolites [33][34][35]. Among several abiotic stresses, salinization of soil increasing continuously and degraded lands all over the globe causes food insecurity by reducing crop productivity [36].…”
Section: Introductionmentioning
confidence: 99%